Our future in public relations : a cautionary tale in three parts - Kerrigan, Ken (Emerald Publishing Limited, 2020)
With more time to communicate than ever before, we find ourselves in a dystopian world where platforms like Facebook, Instagram and Twitter are disintermediating traditional media channels, resulting in the loss of jobs in newsrooms, and creating an era where truth is now in the eye of the beholder. At the same time we are embracing the power of big data and analytics to tell us what business leaders should say and do. Is that the right approach or are we just taking the easy way out? Aimed primarily at communications management professionals, Our Future in Public Relations explores whether the profession of public relations still matters today. Is PR just a new form of marketing or is it more alive and important than ever before, especially as a driver of purpose-driven organizations? In an era of fake news and diminishing trust, it's time to ask exactly what our future in public relations will be., Short description/annotation, In an era of fake news and diminishing trust, it's time to ask exactly what our future in public relations will be. Aimed primarily at communications management professionals, Our Future in Public Relations delves into whether public relations are dead, or rather more important than ever before as a driver of purpose-driven organizations.